P021 Differential clinical and neurophysiological outcomes after premotor rTMS in Parkinson's disease. Issue 3 (March 2017) - Biagioni, M.; Son, A.; Agarwal, S.; Gilbert, R.; Quartarone, A.; DiRocco, A.
Abstract : Question: Weekly sessions of low frequency (LF) repetitive transcranial magnetic stimulation (rTMS) over supplementary motor area (SMA) have shown motor improvement as add-on therapy for Parkinson's disease (PD). We conducted an active-controlled study to explore potential additive effects of rTMS over both SMA and dorsal premotor area (PMd) compared to SMA alone and potential neurophysiological (NPh) correlates. Methods: PD patients with Hoehn & Yahr scores 2–3 participated in a parallel double-blind randomized study of four weekly sessions of LF rTMS. Intervention arms were rTMS over SMA (SMA-alone) and rTMS over both PMd and SMA (PMd + SMA). Clinical outcomes were Unified Parkinson's Disease Rating Scale-III (UPDRS-III) score; axial, tremor, rigidity, and bradykinesia sub-scores. NPh outcomes were motor evoked potentials, cortical silent period (SP), short interval intra-cortical inhibition and intra-cortical facilitation. Outcomes were analyzed at baseline and 4-weeks post-treatment completion. Results: Baseline demographics in Table 1 ; 14 patients completed all study visits. UPDRS-III improved in both arms, SMA-alone (19.8%, p  < 0.05) and PMd + SMA (21.0%, p  < 0.05). SMA-alone significantly decreased bradykinesia sub-scores (BrS) ( z  = -2.21, p  < 0.05) while PMd + SMA decreased both BrS ( z  = -2.0, p  < 0.05) and axial sub-scores (AxS) ( z  = -2.4, p  < 0.05). NPh outcomes revealed significant increase of SP in PMd + SMA vs. SMA-alone ( U  = 7.0, p  < 0.05). Also, the change in SP showed mod-high correlation with the change in AxS when participants were pooled together ( r  = -0.60, p  < 0.05; Fig. 1 ). Other NPh outcomes were not significant. Conclusions: We confirmed weekly LF premotor rTMS can improve motor scores and BrS. AxS improvement seen in the PMd + SMA arm may indicate therapeutic selectivity. As such, the correlation between SP and AxS suggests prolonging SP correlates with improved posture, balance and gait (axial symptoms). As PD patients have shortened SP, this correlation could reflect adequate restorative intra-cortical modulation.